Improving hand surgery access and care through service redesign. Issue 7 (3rd December 2015) - Isedale, Grant; Harris, Ian; Rider, Mark
Abstract: Background: The hand surgery service in our major trauma centre comprised predominantly emergency surgery with poor theatre access, resulting in many cases being postponed and performed after hours and with low rates of supervision. Method: We report the results of a before‐and‐after study describing the change in processes and outcomes associated with a change in the model of care to a sequestered, area‐wide hand surgery service. The study uses data from 12 months prior to and 12 months after the change in practice. Results: The hand service experienced a 24.7% increase in demand for surgery in the first 12 months after the relocation. However, demand for overnight beds fell by 303%, the rate of specialist supervision increased from 23.5% to 81.3% ( P < 0.0001), the time between admission and surgery fell from 5.1 to 2.7 h ( P < 0.0001), the rate of cancellations fell from 21.8% to 7.7% ( P < 0.0001), the proportion of emergency surgery conducted in normal hours increased from 65.8% to 93.6% ( P < 0.0001), the 28‐day unplanned reoperation rate fell from 1.2% to 0.5% ( P = 0.02) and surgical time decreased to an equivalent of 41 half day operating sessions per year. Conclusion: These outcomes are in line with international experiences of service centralization. The project may be used as a template for practice change in other surgical fields.